Spontaneous retroperitoneal hematoma, an uncommon case of acute surgical abdomen in a patient with hemophilia: case report - Martínez-García, Erik; Roman-Chávez, Pedro D.; Martínez-Canseco, Karla A.; Galván-Ortiz, Marco A.; Figueroa-Zariñana, Victor H. (International Journal of Research in Medical Sciences, 2024)
Hemophilia A is an X-linked hereditary disorder with a predilection for men. A worldwide incidence of 1 in 5 000 inhabitants is estimated. Currently, there is no curative treatment, which can lead to the development of multiple complications. However, abdominal presentations related to acute abdomen are uncommon and require surgical treatment. Similar cases are related to psoas muscle hematoma and hemophilic pseudotumors. We presented a 25-year-old male diagnosed with hemophilia A with acute abdominal pain and peritoneal irritation signs. After evaluation, we decided to perform a laparotomy, which reported a hematoma in the right mesocolon from the ileocecal valve to the hepatic flexure with right colic artery disruption. After seven days, he was discharged due to clinical improvement, and we indicated an outpatient general surgery follow-up. Acute abdomen caused by a retroperitoneal hematoma in patients with hemophilia is uncommon. Therefore, its management is still controversial. We concluded that a surgical approach might reduce the risk of complications in patients with poor clinical courses.